2015
DOI: 10.3758/s13414-015-0889-2
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious experiences and detection accuracy while observing pain and touch: The effect of perspective taking

Abstract: In this study, we investigated the effects of observing pain and touch in others on vicarious somatosensory experiences and the detection of subtle somatosensory stimuli. Furthermore, the effect of taking a first-versus a third-person perspective was investigated. Undergraduates (N = 57) viewed videos depicting hands being pricked (pain), hands being touched by a cotton swab (touch), and control scenes (same approaching movement of a hand as in the other video categories, but without the painful/touching objec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 47 publications
3
8
0
Order By: Relevance
“…This is again in line with the findings of other studies demonstrating that observing somatosensation may facilitate somatosensory experiences (e.g. Cardini et al, 2013;Serino et al, 2008;Vandenbroucke et al, 2015). Our results suggest that the different video categories (touch, pain, control) may modulate somatosensation differently.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is again in line with the findings of other studies demonstrating that observing somatosensation may facilitate somatosensory experiences (e.g. Cardini et al, 2013;Serino et al, 2008;Vandenbroucke et al, 2015). Our results suggest that the different video categories (touch, pain, control) may modulate somatosensation differently.…”
Section: Discussionsupporting
confidence: 82%
“…In line with previous research (Vandenbroucke et al, 2015), our results show that participants reported more vicarious somatosensory experiences when pain-related videos were shown compared with control and touch videos. The presentation of touch did not enhance the report of vicarious experiences compared with control videos, illustrating the specific modulatory effects of observing pain compared with touch.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…dummy body parts). Previous behavioural research has also found that viewing touch to hands in a first‐ vs. third‐person perspective can influence task performance (Vandenbroucke et al ., ), but whether visual perspective influences performance change following brain stimulation has not been studied. Additional work is therefore needed to (i) examine the replicability of findings indicating that increasing excitability within the somatosensory system can induce MTS in non‐synaesthete controls and (ii) consider how variations in stimulus presentation (e.g.…”
Section: Introductionmentioning
confidence: 99%